2004
DOI: 10.1016/j.pain.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic post-ischemia pain (CPIP): a novel animal model of complex regional pain syndrome-Type I (CRPS-I; reflex sympathetic dystrophy) produced by prolonged hindpaw ischemia and reperfusion in the rat

Abstract: A neuropathic-like pain syndrome was produced in rats following prolonged hindpaw ischemia and reperfusion, creating an animal model of complex regional pain syndrome-Type I (CRPS-I; reflex sympathetic dystrophy) that we call chronic post-ischemia pain (CPIP). The method involves placing a tourniquet (a tight fitting O-ring) on one hindlimb of an anesthetized rat just proximal to the ankle joint for 3 h, and removing it to allow reperfusion prior to termination of the anesthesia. Rats exhibit hyperemia and ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
354
4
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 287 publications
(381 citation statements)
references
References 66 publications
17
354
4
6
Order By: Relevance
“…34 Furthermore, Coderre et al detected elevated levels of malondialdehyde in the hind paw muscles of the rat and have shown that the animal's pain hypersensitivity is reduced by free radical scavengers and antioxidant therapy. 35,36 Taken together with the previous data, we observed that oxidative stress occurs mainly in CRPS I. Although previous clinical studies have indicated the presence of oxidative stress in CRPS I patients, it has been difficult to prove whether it is a cause or a consequence of CRPS I.…”
Section: Interventional Therapiessupporting
confidence: 73%
See 1 more Smart Citation
“…34 Furthermore, Coderre et al detected elevated levels of malondialdehyde in the hind paw muscles of the rat and have shown that the animal's pain hypersensitivity is reduced by free radical scavengers and antioxidant therapy. 35,36 Taken together with the previous data, we observed that oxidative stress occurs mainly in CRPS I. Although previous clinical studies have indicated the presence of oxidative stress in CRPS I patients, it has been difficult to prove whether it is a cause or a consequence of CRPS I.…”
Section: Interventional Therapiessupporting
confidence: 73%
“…[30][31][32][33] It has been speculated that free radical generation by the mitochondrial respiratory chain contributes to the pathophysiology of CRPS I. [34][35][36] Eisenberg et al demonstrated significant increases in malondialdehyde, lactic dehydrogenase, and antioxidants (peroxidase, superoxide dismutase, uric acid) in the serum and especially the saliva of CRPS I patients compared to healthy controls. 34 Furthermore, Coderre et al detected elevated levels of malondialdehyde in the hind paw muscles of the rat and have shown that the animal's pain hypersensitivity is reduced by free radical scavengers and antioxidant therapy.…”
Section: Interventional Therapiesmentioning
confidence: 99%
“…Chronic postischemia pain was generated after exposure to prolonged hind paw ischemia and reperfusion as described in Coderre et al 14 Briefly, rats were anesthetized over a 3-to 4-hour period with a bolus (40 mg/kg, i.p.) and chronic intraperitoneal infusion of sodium pentobarbital for 2 hours (13 mg/h for the first hour, 6.5 mg/h for the second hour).…”
Section: Animal Model Of Crps-imentioning
confidence: 99%
“…CPIP rats display several features that resemble human CRPS, including edema, hyperemia, and the development of mechanical and cold allodynia without direct nerve injury. 14 The CPIP model has therefore been proposed as animal model for CRPS type-I. The aim of the present study was investigate the involvement of NFkB in CPIP, and potentially the pathogenesis of CRPS, by measuring NFkB levels and assessing the antiallodynic effect of NFkB inhibition by PDTC in rats after IR injury.…”
Section: Introductionmentioning
confidence: 98%